Welfare and competition : the economics of a fully employed economy - Scitovsky, Tibor (London UNwin University Books, 1968)
The aim of this book is to bring together price theory and welfare economics
includes index
ijb, 17/01/2019
Loans
Keywords: Competition; Welfare economics; Welfare and competition